Inverter-parallel Power Supply System for Vehicle and Its Control - LUO Guoyong; LIU Wenping; GAO Lulu; CAO Huaizhi (Kongzhi Yu Xinxi Jishu)
It studied vehicle inverter-parallel power supply system, described the relationship between phase and amplitude error of the system output and active power and reactive output power of the inverter. A scheme of wireless multiple-inverter-parallel operation was presented which adjusted the amplitude and frequency of output voltage through real-time detection and calculation of respective output active power and reactive power of inverters. Experimental results show that the system operates steadily and the validity of this design is verified.